Role-Play Implementation: Nursing Students’ Perspectives to Speak English - Maharani, Mega Mulianing (INDONESIAN JOURNAL OF SUSTAINABILITY, 2024)
Preparing nursing students to have an internship or even to be nurses at international hospital need efforts. One of which is through preparing students to be able to speak in English. English for nursing students is taught at second semester. The students are drilling to speak in English through a role-play. The role-play implemented in a nursing class is about to be a patient and a nurse. In order to know their speaking ability, knowing their perception on its implementation is essential to reach a betterment. In a qualitative approach, the open-ended questionnaire is used to get the data from twenty students participated in the study. The perceptions are focused on both emotional and behavioral state. There are four questions which are two for emotional and two for behavioral state. Following the qualitative data collection and analysis, the researcher finally gets the findings. In conclusion, the students perceive their positive emotional and behavioral state on the implementation of role-play to speak English.